Perils of climate change in the Bay of Bengal: India–Bangladesh in perspective. Issue 3 (2nd September 2019) - Mehta, Simi; Kumar, Vikash
ABSTRACT: While the whole of the globe is and would be affected by climate change at different levels and stages, the Bay of Bengal is one region which is extremely vulnerable and susceptible to the phenomenon and its variability. This paper geographically delineates the key issues of climate change and studies the socio-economic and environmental impact that the fury of climate change has brought to the Bay of Bengal region especially in Bangladesh and India. It adopts descriptive and analytical methods and situates the inquiry in light of the Sustainable Development Goals (SDGs) of the United Nations. The paper provides relevant policy prescriptions as the way forward on adapting the entire gamut of life of humanity to climate change in the region.